From the Renaissance to the Modern World - Peter Iver Kaufman (Guest Editor) (MDPI - Multidisciplinary Digital Publishing Institute, 2013)
On November 11 and 12, 2011, a symposium held at the University of North Carolina in Chapel Hill honored John M. Headley, Emeritus Professor of History. The organizers, Professor Melissa Bullard-Headley's colleague in the department of history at that university-along with Professors Paul Grendler (University of Toronto) and James Weiss (Boston College), as well as Nancy Gray Schoonmaker, coordinator of the Program in Medieval and Early Modern Studies-assembled presenters, respondents, and dozens of other participants from Western Europe and North America to celebrate the career of their prolific, versatile, and influential colleague whose publications challenged and often changed the ways scholars think about Martin Luther, Thomas More, the Habsburg empire, early modern Catholicism, globalization, and multiculturalism. This special issue contains the major papers delivered at the symposium, revised to take account of colleagues' suggestions at the conference and thereafter. John O'Malley studies the censorship of sacred art with special reference to Michelangelo's famed "Last Judgment" and the Council of Trent. John Martin sifts Montaigne's skepticism about contemporaneous strategies for self-disclosure and self-discipline. Stressing the significance of grammar, Constantin Fasolt helps us recapture the Renaissance's and the early modern religious reformations' disagreements with antiquity. Ronald Witt's reappraisal of humanist historiography probes Petrarch's perspectives on ancient Rome. John McManamon includes tales of theft and market manipulation in his study of the early modern collection and circulation of books and manuscripts, the commodification of study. To "nuance" John Headley's conclusions about "the Europeanization of the world," Jerry Bentley repossesses the influence of other than European societies on several European theorists of human rights. Kate Lowe's remarks on the reconstruction of race in the Renaissance explores the effects of a critical mistranslation on what being black was taken to mean by Europeans. David Gilmartin introduces readers to the shape of democracy in nineteenth- and twentieth-century India, as well as to the understandings of popular sovereignty that affected elections, suggesting strides that scholars might take "toward a worldwide history of voting". The remarkable range of these contributions comes close to reflecting the range of Professor Headley's interests and achievements, which James M. Weiss maps in his tribute, identifying "unifying themes" in Headley's work.